Mengungkap Penerapan Sanksi Pelayanan Adat Serta Implementasi Prinsip 5c Sebagai Sistem Pengendalian Internal Dalam Upaya Pencegahan Kredit Macet di LPD Desa Munduk Bestala - Yanti, Putu Ida; Sinarwati, Ni Kadek (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to find out how the credit distribution system at the LPD Desa Munduk Bestala, the internal control system with the application of the 5C principle and the customary service sanctions as an internal control system at the LPD Desa Munduk Bestala, as well as the implications of the application of the 5C principle and the customary service sanctions at the LPD Desa Munduk Bestala. This study uses qualitative methods with descriptive data analysis. Data was collected by observation, interviews and documentation. The results of this study indicate that; 1) The credit system applied by the LPD Desa Munduk Bestala, namely credit is only given to customers from Munduk Bestala village who have a family card and are married with a loan amount of IDR 3,000,000 to IDR 15,000,000,-; 2) LPD assesses the customer according to the 5C principle, if there is a customer who has bad credit then the customary service sanctions are applied to the customer, namely that a certificate of free administration will not be issued by the customary leader and Jero Mangku will not visit the customer when there is a religious ceremony such as death and marriage. 3) The implication is that the implementation of the customary service sanctions and the implementation of the 5C Principles on the internal control system as an effort to prevent bad loans at LPD Desa Munduk Bestala can reduce the occurrence of bad loans.